A Caribbean perspective on China–Caribbean relations: global IR, dependency and the postcolonial condition. Issue 2 (4th November 2020) - Gonzalez-Vicente, Ruben; Montoute, Annita
Abstract: The field of global international relations remains to a great extent aspirational and focussed on the critique of Western-centric perspectives or the appraisal of non-Western theories within their specific geographical and historical contexts. In this essay, we go a step further and transpose a set of Caribbean-based theories that gained prominence in the 1960s and 1970s to apply it to the study of China's contemporary relations with the Caribbean Community, drawing broader implications for China's Belt and Road Initiative. The Caribbean's tradition of critical and radical thought raises important questions about continuing epistemic dependency, structural impediments to development in small and highly open states, and a number of unresolved issues relating to the postcolonial condition in former plantation societies. Drawing upon these insights, we contend that the expectations placed on the emerging 'South–South' link with China are easily overstated, given China's elitist business-centric approach to development, the eschewing of participatory approaches in Sino–Caribbean ventures and the passive incorporation of the Caribbean into China's global vision.